Learning trajectory for equivalent fraction learning: An insight - Adelia, Viona; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Mulyono, Budi (Journal of Honai Math, 2022)
Equivalent fraction is a sub-topic of fractions that highly contributes to explaining the basic concepts of fractions. However, this topic is one of the most challenging topics for students as it involves an advanced and formal concept and various representations. This study aims to present the preliminary result of the learning trajectory on equivalent fractions. This design research consisted of three stages: preparation, implementation, and retrospective analysis. The learning trajectory in the form of a hypothetical learning trajectory (HLT) was designed in the context of measuring cups. The data was collected through documentation, interviews, and class observations. The HLT was implemented to investigate students’ actual learning trajectories. The findings showed that the measuring cup context assists students to easily perceive those different fractions may have the same quantity (equivalent fractions). The learning trajectory consists of two activities. The first one aims to introduce a measurement concept of fractions to students. The second one aims to help students construct the concept of equivalent fractions. Finally, the study findings contribute to further development of learning trajectory on equivalent fractions.